Makna Ritual Paruman Barong di Pura Luhur Natar Sari, Desa Apuan, Kabupaten Tabanan - Bontot, I Nyoman (Widya Duta: Jurnal Ilmiah Ilmu Agama dan Ilmu Sosial Budaya, 2020)
Piodalan ageng ritual in Luhur Natar Sari Temple, its implementation is slightly different from the other temples in general in Bali. A long and complex ritual, beginning with ngelawang ritual to three regencies in Bali, melasti, at the time of the peak of the ritual was attended by dozens of barong and thousands of pemedek. The implementation takes a lot of time, energy and not a small amount for the pemedek involved in the piodalan ageng series. This research proposes three problems, namely the ideology of barong meeting ritual, the form of the barong meeting ritual, and the meaning of barong meeting ritual. The problem is examined with eclectic theory, structuration theory, religious theory, and practical theory.The presence of dozens of barong and thousands of pemedek on piodalan ageng in Luhur Natar Sari Temple, motivated by the existence of three ideologies, namely theological ideology, political ideology, and economic ideology. The form of barong meeting ritual in the sublime Luhur Natar Sari Temple is a series of nangiang Tapakan Ida Bhatara Sakti ceremonies, chanting to jaba kuta for 42 days, bhatara tedun kabeh or barong meeting, penganyaran, barong dance, and closing ceremonies. The meaning of barong meeting ritual in Luhur Natar Sari Temple is a recitation in accordance with history, withnessing the people up close, pasupati begging for taksu, pujawali, and meeting in noetic terms.